A security model of multiparty conference with eavesdropping protection over digital networks - Supachai Tangwongsan (2018)
The purpose of this research is to develop a security model for multiparty conference with eavesdropping protection over digital networks. The proposed model provides an encryption scheme and a key exchange among a communicating group, which is set privately and not specified by the network operator. There are two main processes in the system. The first one is the key exchange within the conversation group, a so-called shared key, by using the group Diffie-Hellman key-exchange protocol (GDH). Furthermore, an encryption rule, a so-called 1:S is set up to define whether full frame or partial frame encryption scheme is used. And the second one is the encryption of voice data packet during the conversation that is possibly encoded with various standards. The results of the implementation show that the system could perform its function accurately as designed. In this regard, the proposed system is suitable for effective use in multiparty conference with eavesdropping protection over digital networks, without any requirements to modify for changes in presently existing network systems, mobile phone network and VoIP, for instance. © 2008 IEEE.